Glomerular Hematuria: Cause or Consequence of Renal Inflammation? - Moreno, Juan Antonio (Int J Mol Sci, 2019)
Glomerular hematuria is a cardinal symptom of renal disease. Glomerular hematuria may be classified as microhematuria or macrohematuria according to the number of red blood cells in urine. Recent evidence suggests a pathological role of persistent glomerular microhematuria in the progression of renal disease. Moreover, gross hematuria, or macrohematuria, promotes acute kidney injury (AKI), with subsequent impairment of renal function in a high proportion of patients. In this pathological context, hemoglobin, heme, or iron released from red blood cells in the urinary space may cause direct tubular cell injury, oxidative stress, pro-inflammatory cytokine production, and further monocyte/macrophage recruitment. The aim of this manuscript is to review the role of glomerular hematuria in kidney injury, the role of inflammation as cause and consequence of glomerular hematuria, and to discuss novel therapies to combat hematuria.